Šport kot socialna arena nacije v Sloveniji - Starc, Gregor (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
SPORTS AS SOCIAL ARENA OF NATIONAL IDEA IN SLOVENIA. Ever since its emergence in the 19th century modern sports have been inseparably linked to the idea of nation and processes of its creation, the case of Slovenia being no exception.In this respect sports can be understood from the perspective of Halbwachs' idea of inventing the tradition, as also in the Slovene territory the idea of national sports, the roots of which are intertwined with the rootsof the nation itself, began developing early. Emotional responses of people to sports results are constantly pervaded by a growing sense of adherence to a certain imagined community at local or national level, which is primarily a consequence of the development of media as the elementary system of synchronous mass communication. Sports arena has been the place of intensive processes of national identification and dis-identification, which have been establishing a seemingly sharp yet very flexible and inconsistent boundary line between members of the imagined Slovene nation and others.
Keywords: Slovenia; Slovenija; nacionalizem; nationalism; sport; šport; narodna identiteta; communication medium; mediji